PARTISIPASI POLITIK NU DAN KADER MUSLIMAT DALAM LINTAS SEJARAH - Munawir Haris (AL-TAHRIR, 2015)
Abstract: Political movement of Nahdhatul Ulama’ (NU) as a religious organization and NU Women Cadre (Muslimat NU) as an autonomous body appeared in the trajectory of the national history. The problem that arised was that to what the extent NU had  participated in national politics and how big Muslimat NU’s representation was in national politics. Through a typology approach, this article explored the political contributions of NU and NU Women Cadre in the trajectory of the national history. A lot of data indicated that NU and muslimat NU had taken part both passively and actively in national politics. In the colonial era, typologically NU took part as passive participant, but in the next period, it took part in the form of non-conventional active participants.This active participant apparently showed its participation when NU issued Jihad Resolution to defend Indonesian independence. Its participation was then allied   with Masjumi, but then it built its own political party independently. The passive participation of  NU Women Cadres (Muslimat) began to be recognized in 1938, and then it just began to be recognized as active participant in 1946.  Women of NU became active participants to promote gender equality in 1954. Five years later, it became galdiator participant, and began to show its gender roles simultaneously by raising the strategic issues aimed at enforcing the rights, resources of human being and aspirations for women to participate in public life, including practical politics.الملخص :ظهرت الحركة السياسية لنهضة العلماء كجمعية دينية والمنظمة التابعة لها " المسلمات" عبر التاريخ. والسؤال المطروح هو ما مدى اشتراك "نهضة العلملاء" في السياسة الوطنية ومدى وكليّة المسلمات في المجال السياسي. حاولت هذه المقالة – بالمدخل التجنيسي – دراسة الاسهام السياسي  ل"نهضة العلماء" و "المسلمات" في تاريخ الشعب الإندونيسي. دلّت البايانات المتنوّعة على أن جمعية "نهضة العلماء " و " المسلمات " اشتركتا اشتراكا مباشرا وغير المباشر في السياسة الوطنية، لكنّ في المرحلة بعدها اتّخذت شكل الاشتراك المباشر غير التقليدية. ظهر هذا الاشتراك المباشر حيث أعلن مشروعية الجهاد لحماية استقلال إندونيسيا. وكان هذا الاشتراك   عن طريق حزب "ماشومي" وفي المرحلة بعدها أسس الحزب السياسي مستقلا. بدأ الاشتراك غير الماشر ل"المسلمات" سنة 1938ويُعدّ اشتراكها مباشرا بداية من السنة 1954م. وفي السنوات الخمس بعد هذه المرحلة أصبحت هي جمعية مشاركة وعرضت دورها الجنسي متواصلا بطرح المسائل المهمة تهدف إلى تقوية حقوق المرأة، وموارد القوّة لها، واختياراتها للاشتراك في المجتمع وفي مجال السياسة.Abstrak: Gerakan politiik NU sebagai sebuah organisasi keagamaan dan Muslimat NU sebagai badan otonom nampak dalam lintasan sejarah bangsa. Problem yang muncul adalah sejauh mana partisipasi NU dalam politik nasional dan seberapa besar keterwakilan muslimat NU dalam politik. Melalui pendekatan tipologi, Tulisan ini akan mengeksplorasi kontribusi politik NU dan Muslimat NU dalam lintasan sejarah bangsa. Beragam data menunjukkan bahwa NU dan muslimat NU berpartisipasi pasif dan aktif dalam politik nasional. Pada masa kolonial NU masuk dalam tipologi partisipan pasif, namun dalam masa berikutnya mengambil bentuk partisipan aktif yang non-konvesional. Partisipan aktif ini nampak jelas ketika NU mengeluarkan Resolusi Jihad untuk mempertahankan kemerdekaan. Partisipasi ini kemudian disalurkan melalui Masyumi, lalu mendirikan parpol secara mandiri. Partisipasi pasif Muslimat NU mulai diakui pada tahun 1938, dan baru diakui sebagai partisipan aktif pada tahun 1946. Muslimat menjadi partisipan aktif yang memperjuangkan kesetaraan gender pada tahun 1954. Lima tahun kemudian Muslimat menjadi galdiator participant, dan mulai menunjukkan peran gendernya secara simultan dengan mengangkat isu-isu strategis yang bertujuan untuk penguatan hak, sumber daya dan aspirasi bagi perempuan untuk berpartisipasi di ranah publik termasuk politik praktis.Keywords: NU, muslimat, partisipasi, politik, Indonesia.